2004
DOI: 10.1097/00002030-200401230-00003
|View full text |Cite
|
Sign up to set email alerts
|

Recombination following superinfection by HIV-1

Abstract: Intersubtype recombination took place between the original non-recombinant subtype A strain and the superinfecting subtype C strain in an untreated, chronically infected woman. This finding helps to explain the rising prevalence of recombinant HIV-1 worldwide. Recombination resulting from superinfection with diverse strains may pose problems for eliciting broad immune responses necessary for an effective vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 30 publications
3
76
0
3
Order By: Relevance
“…However, superinfection may be difficult to detect when the superinfecting virus is of the same subtype as the initial virus, and the detection of possible consequent recombinants is restricted to a handful of reports. [2][3][4][5][6] It has previously been reported that superinfection with a virus of different subtype can result in replacement of the original virus. 2,7-9 Fang et al 4 showed replacement of subtype A virus with AC, but did not show the presence of ''pure'' subtype C virus, so the superinfection could have been with an AC recombinant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, superinfection may be difficult to detect when the superinfecting virus is of the same subtype as the initial virus, and the detection of possible consequent recombinants is restricted to a handful of reports. [2][3][4][5][6] It has previously been reported that superinfection with a virus of different subtype can result in replacement of the original virus. 2,7-9 Fang et al 4 showed replacement of subtype A virus with AC, but did not show the presence of ''pure'' subtype C virus, so the superinfection could have been with an AC recombinant.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] It has previously been reported that superinfection with a virus of different subtype can result in replacement of the original virus. 2,7-9 Fang et al 4 showed replacement of subtype A virus with AC, but did not show the presence of ''pure'' subtype C virus, so the superinfection could have been with an AC recombinant. Others have reported dual infection 10 or superinfection 3,5,6 with the same subtype followed by recombination.…”
mentioning
confidence: 99%
“…weight loss, tuberculosis and cryptococcal infection appeared and she died in 1998, e.g. over 14 years after her primary HIV-1 infection (Fang et al, 2004). In this cohort of sex-workers, mean survival was 4.4 years, and surviving over 10 years was rare, suggesting that this woman had a remarkably slow disease progression despite an HIV-1 superinfection in the chronic phase of the infection.…”
Section: Superinfection Cases With Low or Normal Clinical Progressionmentioning
confidence: 80%
“…Unfortunately, she was lost to follow-up after she died in 2001 from obstetric complications. A superinfected Kenyan female sex worker from the pre-antiretroviral therapy period was presented by Fang et al (2004). In February 1985, this patient from Nairobi tested HIV-1 seropositive and was, retrospectively, found to be infected with a subtype A strain.…”
Section: Superinfection Cases With Low or Normal Clinical Progressionmentioning
confidence: 99%
“…Indeed, a sudden increase in viral load accompanied with symptoms of primary HIV-1 infection revealed an interclade superinfection in two IDUs who were defined as controllers after the initial infection with subtype B and CRF11 HIV-1 strains, respectively. Similarly, superinfection led to febrile illness and disease progression in an HIV-1-positive untreated female sex worker who presented normal CD4+ T cell counts and low viremia for about 5 years prior to a secondary productive HIV-1 infection [74]. However, the mechanisms underlying the loss of viral control in these unique cases are not clear as the authors did not investigate HIV-1-specific humoral and cellular responses, nor did they look at the replication capacity of the initial virus.…”
Section: Impact Of Hiv-1 Superinfection On the Spontaneous Control Ofmentioning
confidence: 99%